Analysis of cardiovascular risks in practitioners of unsupervised exercises - Renata Cristina Oliveira Penha; Danielle Silva Yamamoto; Isabel Aparecida Porcatti de Walsh; Gualberto Ruas; Marilita Falangola Accioly
Introduction Physical exercise is recommended by health professionals for the prevention of cardiovascular events; for it is important that practitioners follow recommendations of qualified professionals. Objectives To analyze the cardiovascular risks and the physical exercise of regulars of a municipal public park. Materials and methods 110 regulars of a municipal public park were evaluated by questionnaire and physical examination, 60 men and 50 women with a mean age of 48.8 ± 11.76 years. Cardiovascular risk was classified according to the American Table and physical activity following the recommendations of the American College of Sports Medicine and the American Heart Association. Results Regarding the classification of cardiovascular risk, 54% of the studied population presented potential risk and 31% moderate. As for physical exercise, 58% were considered inactive, 14% active and 28% were very active. 90% received no professional guidelines. Conclusion The public park goers have cardiovascular risk and do exercise without individualized guidance.